The use of mobile technology to support work integrated learning in undergraduate nursing programs: An integrative review. (September 2022) - Wilson, D.; Aggar, C.; Massey, D.; Walker, F.
Abstract: Objectives: Investigate the use of mobile technology to support Work Integrated Learning in undergraduate nursing programs. Design: Integrative review with narrative synthesis. Data sources: Electronic databases searched in February 2021 included CINAHL, ERIC, MEDLINE and APA PsychInfo. Review methods: The methodological framework described by Whittemore and Knafl (2005) guided this integrative review. A total of five (5) studies published between 2017 and 2020 were analysed and synthesised. Results: Data was categorised into two themes: 1) Accessibility of Learning Resources, and 2) Effective and Timely Communication. Convenient and easy access to Learning Resources at the point of care improved students' confidence and competence to perform clinical skills, thereby reducing student's anxiety and increasing satisfaction rates. The accessibility to educational and skills-based resources also promoted patient safety at the point of care. Effective and Timely Communication improved engagement and collaboration between students, clinical facilitators and academics, enabling a more supportive environment that improved student autonomy and motivation for self-directed learning. The Effective and Timely Communication of student progression and assessment strategies was found to improve student engagement and motivation to be independent learners. Conclusion: This review contributes important knowledge because internationally there is a need to increase knowledge and understanding of how to best support Work Integrated Learning experiences of student nurses. Mobile technology has been recognised as an innovative tool in education, further research investigating its use to support Work Integrated Learning in undergraduate nursing programs is required. Highlights: Mobile technology can be used to support undergraduate nursing students whilst on WIL Mobile technology in WIL was found to support effective and timely communication Mobile technology improves accessibility of learning resources, and supports students' satisfaction with WIL